THE ROLE OF TGF-Î²1 IN THE DEVELOPMENT OF DIABETIC NEPHROPATHY EXPERIMENTALLY INDUCED BY STREPTOZOTOCIN AND THE NEPHROPROTECTIVE EFFECTS OF CANDESARTAN - Trojacanec, Jasmina; Pavlovska, Kristina; Shikole, Emilija; Kolovchevski, Nikola; Labachevski, Bojan; Nikodinovski, Aleksandar; Jakjovski, Krume; Kikerkov, Igor; Petrusevska, Marija; Zdravkovski, Panche; Zafirov, Dimche (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Diabetic nephropathy (DN) stands as a prevalent and severe complication of diabetes mellitus (DM), lacking adequate medical therapy. The molecular mechanisms contributing to glomerular membrane damage involve the overactivity of angiotensin II, heightened expression of nephrin, vascular endothelial growth factor (VEGF), and notably, intraglomerular transforming growth factor TGF-Î²1. Pharmaceutical treatments targeting hemodynamic disturbances in diabetic nephropathy, such as ACE inhibitors and angiotensin receptor blockers (ARBs), hold promise for DN therapy. This study aimed to assess the role of intraglomerular TGF-Î² expression in experimentally induced DN in rats and explore the nephroprotective effects of candesartan. Diabetes mellitus was induced through a single intraperitoneal injection of streptozotocin (STZ) at 60 mg/kg, and DN was allowed to develop over four weeks. DM rats were randomly assigned to two groups: STZ (untreated) and STZ+CAN (treated with candesartan at 5 mg/kg/day from week 4 to week 12). STZ administration led to a substantial increase in TGF-Î²1 expression in the glomeruli, exceeding control levels by 5-6 times. Candesartan treatment demonstrated a significant reduction in glomerular proliferation and subsequent expansion of the mesangial matrix, suggesting a potential mechanism by which these drugs achieve therapeutic effects. Key words: Streptozotocin, Diabetic nephropathy, TGF-Î²1, Candesartan, Rats.